An Improved NSGA-III Algorithm for Scheduling Ships Arrival and Departure the Main Channel of Tianjin Port - Luzhen Ren; Yuzheng Li; Shibo Zhou (IEEE Access)
An effective scheduling method for ship arrival and departure is crucial for maximizing port resources and improving waterway navigation efficiency. In order to enhance the efficacy of ship arrival and departure scheduling, a scheduling model is developed with the objective of minimizing the total scheduling time and minimizing the total waiting time of the ship. Furthermore, an enhanced three-generation non-dominated sorting genetic algorithm, NSGA-III, is proposed as a solution to the ship scheduling model. The improved NSGA-III algorithm employs the Metropolis criterion in the simulated annealing algorithm in conjunction with the small habitat technique to optimize the initial population of NSGA-III. Additionally, it utilizes a multi-objective parallel strategy and an adaptive cross-variation strategy to enhance the convergence ability and robustness of NSGA-III, thereby preventing it from falling into a local optimum. The improved NSGA-III is employed to resolve the scheduling model under disparate operational conditions within the primary channel of Tianjin Port. The algorithm’s efficacy is evaluated in comparison to the classical NSGA-II and NSGA-III algorithms. The results show that the im-proved NSGA-III algorithm is better than the NSGA-II and NSGA-III algorithms. The optimal scheduling plan for ship entry and exit in the main channel of Tianjin Port and the sequence of ship arrival and departure scheduling were obtained by Pareto solving set and combining with Topsis evaluation method. The method proposed in this paper offers a novel approach to the optimization of ship arrival and departure scheduling.